Further genetic and clinical insights of posterior polymorphous corneal dystrophy 3 - Liskova, Petra; Palos, Michalis; Hardcastle, Alison J; Vincent, Andrea L (JAMA ophthalmology, 2013)
IMPORTANCE: Posterior polymorphous corneal dystrophy (PPCD) is a very rare disorder characterized by primary changes of the posterior corneal layers. Sequence variants in 3 genes are associated with the development of PPCD, including ZEB1 that is responsible for PPCD3. Evidence suggests at least 1 more gene remains to be identified. OBJECTIVE: To determine the molecular genetic cause of PPCD3. DESIGN: We performed extensive ophthalmological examination, including rotating Scheimpflug imaging technology and specular microscopy, and direct sequencing of the ZEB1 coding region. Comprehensive review of published PPCD3-causing variants was undertaken. SETTING: Ophthalmology department of a university hospital. PARTICIPANTS: Four Czech probands. MAIN OUTCOMES AND MEASURES: Results of ophthalmological examination and direct sequencing of the ZEB1 coding region. RESULTS: The following 2 novel frameshift mutations within ZEB1 were identified: c.2617dup in exon 8 in a 22-year-old woman, considered to be most likely de novo in origin, and c.698dup in exon 6 in a 20-year-old man. The first patient had mild changes consistent with PPCD and bilateral best-corrected visual acuity of 1.00. The corneal phenotype of the patient in the second case was more severe, with best-corrected visual acuity of 0.40 OD and 0.05 OS. Corneas of both probands were abnormally steep (keratometry readings, flat ≥ 47.4 diopters [D] and steep ≥ 49.2 D) with increased pachymetry values but no pattern indicative of keratoconus. Specular microscopy in both patients revealed reduced endothelial cell density (range, 1055/mm² to 1655/mm²). Both probands had a history of surgery for inguinal hernia; the male patient also reported hydrocele. CONCLUSIONS AND RELEVANCE: Nucleotide changes within the coding region of ZEB1 underlie the pathogenesis of PPCD in 4 of 23 Czech probands (17%). The cumulative de novo ZEB1 mutation rate is at least 14%. Possible involvement of ZEB1 sequence variants not readily identified by direct sequencing of coding regions needs to be further investigated. Our findings also have implications for patient counseling.
Keywords: Corneal Dystrophies, Hereditary; Corneal Pachymetry; exony; Humans; Frameshift Mutation; rohovkový endotel; Transcription Factors; Female; mladý dospělý; Zinc Finger E-box-Binding Homeobox 1; Phenotype; Exons; počet buněk; dědičné dystrofie rohovky; lidé; Homeodomain Proteins; nitrooční tlak; posunová mutace; molekulární biologie; Corneal Endothelial Cell Loss; transkripční faktor Zeb1; ženské pohlaví; Male; rohovková topografie; Corneal Topography; fenotyp; homeodoménové proteiny; polymerázová řetězová reakce; Polymerase Chain Reaction; Young Adult; úbytek endoteliálních buněk rohovky; transkripční faktory; mužské pohlaví; Molecular Biology; Visual Acuity; Intraocular Pressure; pachymetrie rohovky; zraková ostrost; Cell Count; Endothelium, Corneal